Musa markkuana stat. nov. (Musaceae)—A reassessment of Musa velutina subsp. markkuana - Hareesh, V. S.; Joe, A.; Sreejith, P. E.; Sabu, M. (Phytotaxa, 2017)
Musa velutina subsp. markkuana was published based on morphological characters. Present studies on anatomy of lamina, midrib, petiole, bract, fruit peel and seeds, palynology and micromorphology of seeds of M. velutina and M. velutina subsp. markkuana have revealed that the differences are strong enough to treat the subspecies to species level, M. markkuana stat. nov. Photomicrographs of all parts and comparison charts are provided.